2020
DOI: 10.3390/electronics9081266
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Reliability of Components Subjected to Harmonics Generated by Power Electronic Converters

Abstract: This paper aims at refining an experimentally based reliability model for the insulation of power components subjected to the randomly varying harmonics generated by power electronic converters. Compared to previous papers of the same authors and to the existing literature, here the model is re-formulated from the theoretical viewpoint focusing on the foremost role played by low percentiles of time to failure—in particular by the 1st percentile—selected as the rated life in the framework of modern probabilisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This may interact with the capacitance and inductance of the system. Therefore, the generated harmonics is one of the major concerns and challenging issues that leads the male functioning of the connected and protection systems, and reliability concerns of devices and components in the power system [2]. They also increase the neutral current in a three-phase power system [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This may interact with the capacitance and inductance of the system. Therefore, the generated harmonics is one of the major concerns and challenging issues that leads the male functioning of the connected and protection systems, and reliability concerns of devices and components in the power system [2]. They also increase the neutral current in a three-phase power system [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that improved performances can be achieved with EMs designed for higher rated voltages. CSIs feature low output voltage THD and favourable dv/dt, which applies less stress on EM terminals and prevents winding insulation ageing [34] and insulation failure [35]. These features, combined with their voltage boosting characteristics, make CSIs a viable choice for low DC voltage transport drives [14].…”
Section: Introductionmentioning
confidence: 99%
“…Reliability is more and more a key problem in engineering, especially in the field of electronics, as witnessed by a recent special issue on this topic, focused on Power electronic devices reliability [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Nowadays, indeed, these are becoming more and more critical devices, since-as highlighted in [16]-ower electronics plays a crucial role in renewable energy systems, lighting, electric mobility, and other systems that enable sustainable development.…”
Section: Introductionmentioning
confidence: 99%